Posted by Willy Wonka on Wednesday, May 4, 2011 at 11:57pm.
25s + 25 = -15s
first, we transpose all terms containing the variable s to one side of the equation (in this problem, let's transpose them to the left side), and all other terms to the other side.
thus, we transpose -15s to the left side. to transpose, we change its sign to the opposite, thus it becomes +15s on the left side, and the +25 becomes -25 on the right:
25s + 25 = -15s
25s + 15s = -25
then we combine similar terms. to combine terms with variables, we just add the numerical coefficient (the number before the variable), thus it becomes:
40s = -25
finally to get s alone, we divide both sides of equation by 40:
(40s)/40 = -25/40
s = -5/8
hope this helps~ :)